Filippo Grandi Reports on Rohingya Refugee Crisis In Bangladesh: Engagement Evaluation (e-Journal of Linguistics, 2020)
This study concerns with the use of Appraisal Theorydeveloped by Martin & White (2005), under subsumed ofengagement system domain. The engagement system dealswith dialogic perspective between speakers and listeners,which is influenced by the approach of Bakhtin/ Voloshinov,called heteroglossia. Heteroglossic backdrop reveals theproposition lies behind what is stated. In this study, a verbalinteraction between speaker and listener is presented in theform of press conference release. Currently serving HeadCommissioner of United Nations High Commissioner forRefugees (UNHCR), Filippo Grandi, held a press conferencerelease containing of his visiting report to the camp shelter ofRohingya refugee in Bangladesh. The press conferencerelease is a recorded-video type one, which hasapproximately 27:30” in length. It is led by a moderator,reported by the Head Commissioner and joined by 6 follow-up questions. Regarding to engagement system used, theutterances are then transcribed into a transcript, thus it gainsapproximately 395 clauses, moreover, only the utterancesspoken by the Head Commissioner taken as the engagementlocution realizations. The objectives of this research fall intothree: a) to find out the most predominant heteroglossicbackdrop Grandi encodes; b) to recognize the values andviewpoint Grandi intends to convey in his report; and c) toidentify the authorial voice Grandi uses in addressing hisbeliefs of the Rohingya refugee crisis to the audiences. Thequalitative descriptive method is applied. It is found thatcontract-disclaim-counter dominates the report by accountsof 55 realizations. It implies that the facts, Grandi reportsmay against audiences’ expectation, yet in another clause, hedescribes the situation which can reform audiences’ differentviewpoints toward the crisis.)
Keywords: Appraisal Theory; Engagement System; Rohingya Crisis; UNHCR; Filippo Grandi